Use of Ultra-Deep Sequencing in a Patient with Tuberculous Coxitis Shows Its Limitations in Extrapulmonary Tuberculosis Diagnostics: A Case Report - Zhang C; Hu T; Xiu L; Li Y; Peng J (Infection and Drug Resistance, 2019)
Chi Zhang,1,* Tao Hu,2,* Leshan Xiu,1 Yamei Li,1 Junping Peng1 1NHC Key Laboratory of Systems Biology of Pathogens, Institute of Pathogen Biology, Chinese Academy of Medical Sciences & Peking Union Medical College, Beijing, People’s Republic of China; 2Department of Neurosurgery, Shanxi Provincial People’s Hospital, Taiyuan, People’s Republic of China*These authors contributed equally to this workCorrespondence: Junping PengNHC Key Laboratory of Systems Biology of Pathogens, Institute of Pathogen Biology, Chinese Academy of Medical Sciences & Peking Union Medical College, No. 6, Rongjing East Street, BDA, Beijing, People’s Republic of ChinaTel/Fax +86 10 67878493Email pengjp@hotmail.comAbstract: Unbiased metagenomic next-generation sequencing (mNGS) has been widely applied in clinical microbiology for infectious disease diagnostics. Some successful applications in central nervous system infections and respiratory tract infections have proved it to be a promising tool for pathogen detection. Here, mNGS was used to confirm the infectious etiology in a case of tuberculous coxitis, which is a common type of extrapulmonary tuberculosis (TB). A 77-year-old Asian male presented with hip pain and fever was diagnosed with smear- and culture-negative tuberculous coxitis based on the evidence of imaging and interferon-γ release assay. At the same time as the anti-TB therapy started, the patient underwent joint clearance surgery. Whole blood and synovial fluid sampled from surgery were kept for bacteriological confirmation using mNGS with high sequencing depth. However, only two paired-end reads from synovial fluid samples were identified as Mycobacterium tuberculosis. Before leaving hospital, the patient was still receiving anti-TB treatment and began to recover. Considering the obvious escalation of the cost and analysis time as the depth of sequencing increases, although we got a positive result here, the scarce number of reads obtained through ultra-deep sequencing indicates its limitations in extrapulmonary tuberculosis.Keywords: extrapulmonary tuberculosis, metagenomics, molecular diagnostic techniques, Mycobacterium tuberculosis